Population Genetics Provides Insights Into the Impact of Future Climate Change on the Genetic Structure and Distribution of Asian Warty Newts (Genus Paramesotriton) - Dung Van Tran; Tomoya Suzuki; Ibuki Fukuyama; Ricardo J. Vera; Kanto Nishikawa (Ecology and Evolution)
ABSTRACT Assessing population vulnerability to climate change is essential for informing management and conservation strategies, particularly for amphibians. We integrated population genetics and ecological niche modeling (ENM) to assess the effect of climate change on the distribution and genetic structure of two species of Asian warty newts (Paramesotriton deloustali and P. guangxiensis) in northern Vietnam. We analyzed population genetics using a genome‐wide SNP dataset generated with the MIG‐seq method. Additionally, we applied ensemble ecological niche modeling (ENM) to predict the potential distribution of warty newts under two climate change scenarios (SSP2‐4.5 and SSP5‐8.5) for the periods 2050 and 2090. Population genetics revealed three primary groups: West, East + Cao Bang (CB), and Quang Ninh (QN). CB exhibited discordance between mitochondrial DNA and single‐nucleotide nuclear DNA polymorphism data. Furthermore, gene flow within populations was restricted, particularly within West and QN. Spatial distribution analyses of genetic clusters conditioned by environmental variables predicted that the East + CB genetic cluster would expand, whereas those of West and QN would decrease. The introgression of genetic structures probably reduces the vulnerability of East + CB to climate change. ENM analysis revealed that these newts are susceptible to climate change, resulting in a reduction in their suitable habitat areas across all scenarios. We also observed a shift in the suitable distribution toward higher elevations. Our results suggest that the mountainous areas of northern Vietnam could serve as potential refugia for these newts as the effects of climate change intensify.